The impact of social capital in enhancing the psychological empowerment of workers Applied research in the Directorate of the Municipality of Samawah - سعيد, سناء عبد الرحيم; ردام, اركان عبد الله (Journal of Economics and Administrative Sciences, 2018)
The current research aims to study social capital and its effect in enhancing the psychological empowerment of workers through the two variables of social capital within its dimensions (structural, relational, cognitive) and the variable of psychological empowerment within its components (ability, meaning, personal will and influence). The questionnaire was used as a main tool in the collection of data and with data collected from a sample of 168 employees in the Municipality of Samawa Municipality, which is part of the Ministry of Construction, Housing, Municipalities and Public Works. The results of the research (The impact of social capital in enhancing the psychological empowerment of workersApplied research in the Directorate of the Municipality of Samawah) will be presented and analyzed by presenting the computation community to diagnose sample responses, standard deviations to estimate the extent of dispersion in the responses, and the coefficient of variation to determine the degree of homogeneity in the responses of the sample The level of response is limited to  (1 - 5) and five levels according to the categories. The research hypotheses were: (a relationship of correlation and relationship of social capital and empowerment) Psychological Workers), And the research concluded that a constructive confidence of importance and value exists in the teams within the organization, with the need to extend this confidence to customers and processors, and not limited to working individuals. This means that the high confidence is the result of successful collective work in this organization and An important component of social capital as it can produce a functional commitment, group organization, high flexibility of work and can create an environment conducive to the psychological empowerment of the employees of the organization in question. The most important recommendations were focused on the analyzes include the psychological aspect of the workers. The goals for Organization and sense of power and assimilation describe the concept of psychological empowerment that addresses the feelings of staff and can enhance the efficiency of the organization by improving the atmosphere within the organization.